1989
DOI: 10.1002/1097-0142(19890701)64:1<43::aid-cncr2820640109>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Cell culture of small round cell tumor originating in the thoracopulmonary region. Evidence for derivation from a primitive pluripotent cell

Abstract: The authors describe a 14-year-old girl with small round cell tumor originating in the chest wall analyzed by the extensive studies including light and electron microscopic examination, histochemical study, immunochemical study, cytogenetics, and gene analysis. A cell line producing carcinoembryonic antigen (CEA) and neuron-specific enolase (NSE) has been established from pleural effusion of the pulmonary metastatic tumor. Cytogenetic analysis disclosed a reciprocal translocation (11;22)(q24;q12). Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…About 10% of cases with ESFT express EWS-ERG (Kaneko et al 1997). The translocation t(11;22)(q24;q12) was also detected in the reported EES cell lines (Whang-Peng et al 1986;Fujii et al 1989;Homma et al 1989). Karyotype analysis of our established EES1 revealed chromosomes with translocation of t(11;22)(q24:q12).…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…About 10% of cases with ESFT express EWS-ERG (Kaneko et al 1997). The translocation t(11;22)(q24;q12) was also detected in the reported EES cell lines (Whang-Peng et al 1986;Fujii et al 1989;Homma et al 1989). Karyotype analysis of our established EES1 revealed chromosomes with translocation of t(11;22)(q24:q12).…”
mentioning
confidence: 56%
“…There were no significant associations between cytokeratin expression and each of the following parameters: patient age, sex, skeletal and extraskeletal primary site. Fujii et al (1989) and Llombart-Bosch et al (1990) reported positivity of their established EES cells for cytokeratin. In the present case, the primary tumor did not express keratin but the xenograft was reactive with keratin.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Immunoglobulin (Ig) subclass monoclonal antibodies were determined by immunodiffusion by rabbit anti-mouse Ig subclass antisera (BIO RAD Laboratories). Source of tumours Surgically resected human tumours, tumours maintained in a nude mice heterotransplantation system and human cell lines maintained in culture medium were used in this study (Table I) Medicine, Shizuoka;Fujii et al, 1989). shown to have chromosomal translocation with t(I 1; 22).…”
Section: Methodsmentioning
confidence: 99%